1988
DOI: 10.4141/cjas88-127
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Physiological Development of the Reproductive and Adrenal Axis of the Gilt From Weaning to Puberty

Abstract: physiological development of the reproductive and adrenal axis of the gilt from weaning to puberty. Can. J. Anim. Sci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…Hence, the biometrical data of the reproductive tract presented herein may reflect the similar growth pattern reported by Evans et al. () and Almeida et al. ().…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, the biometrical data of the reproductive tract presented herein may reflect the similar growth pattern reported by Evans et al. () and Almeida et al. ().…”
Section: Discussionsupporting
confidence: 89%
“…Recent data on pre-pubertal female pigs showed that despite differences in body weight at slaughter between high and low birthweight gilts, weight and length of the genital tract, or their relative weights, were not affected by birthweight, suggesting that size of reproductive organs is not affected by body size (Almeida et al, 2015). Hence, the biometrical data of the reproductive tract presented herein may reflect the similar growth pattern reported by Evans et al (1988) andAlmeida et al (2015). Indeed, the key to good reproductive performance and high prolificacy during the productive life of the sow is proper genital tract development (Martin Rillo, 1997).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Data indicating that uteri of gilts ovariectomized on neonatal Day 20 continue to grow to Day 180 [22] support the idea that nonovarian factors affect porcine uterine growth throughout this period. Moreover, no clear relationship exists between patterns of growth of adrenal or thyroid glands and gross aspects of reproductive tract growth in gilts between weaning and puberty [45]. These observations reinforce the idea that factors of local origin may be essential for support of uterine wall development in the neonatal pig.…”
Section: Discussionmentioning
confidence: 66%
“…In this regard, consideration must also be given to the fact that signaling through the ER can originate directly, via estrogen-dependent activation [12], or indirectly, through crosstalk between membrane-mediated signal transduction systems and the ER [13]. It is not likely that the neonatal porcine uterus is exposed to more than negligible levels of circulating estrogens [27,28]. Similarly, it does not seem likely, given probable limitations of substrate, that the neonatal endometrium might acquire the ability to synthesize estrogen, although aromatase expression is documented for the porcine endometrium [29,30].…”
Section: Discussionmentioning
confidence: 98%